The LKB1 complex-AMPK pathway: the tree that hides the forest - Sebbagh, Michael (Springer, 2011)
Initially identified as the Caenorhabditis elegans PAR-4 homologue, the serine threonine kinase LKB1 is conserved throughout evolution and ubiquitously expressed. In humans, LKB1 is causally linked to the Peutz-Jeghers syndrome (PJS) and is one of the most commonly mutated genes in several cancers like lung and cervical carcinomas. These observations have led to classify lkb1 as tumour suppressor gene. Although considerable dark zones remain, an impressive leap in the understanding of LKB1 functions has been done during the last decade. Role of LKB1 as a major actor of the AMPK/mTOR pathway connecting cellular metabolism, cell growth and tumorigenesis has been extensively studied probably to the detriment of other functions of equal importance. This review will discuss about LKB1 activity regulation, its effectors and clues on their involvement in cell polarity.